The study of transportation costs for Latex Pillows of Agricultural Community Enterprise in Southern Thailand delivered to the shop in Phuket. - Chodchuang, Naruemon; Suthummanona, Sakesun; Penjumrus, Pallapat; Auckara-aree, Kanya (Thai Industrial Engineering Network Journal, 2019)
This research aims to create a model for analysis and find the cost of distributing latex pillow products from manufacturers that are farmers community enterprises south of Thailand sent to customers who sell latex pillow products in Phuket by developing a mathematical model for selecting the manufacturer. By using the mathematical model generated with excel solver Platform analyzed to get the lowest total cost of delivery. It was found that The cost of transporting latex pillows with a 4-wheeler truck is 150,659.76 baht, which is lower than the cost of transportation by express mail with a cost of 817,400 baht (81.57%) and the cost of shipping with registered mail is 335,000 baht (22.55%). This research aims to help merchants see the opportunity to order products from farmers groups who producing rubber pillows and creating additional value from in the area so that farmers in the southern region have income.